Analysis of E-Government Implementation in Improving the Quality of Public Services (Case Study: Investment Office And Integrated Licensing Services One Provincial Door North Sumatra) - Sitanggang, Romauli; Irawan; Miftha Rizkin (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
The purpose of this study is to analyze the implementation of e-government and contribute to the improvement of the public service system in North Sumatra Province. This study aims to answer the question of how the implementation of e-government has been carried out by the DPMPPTSP of North Sumatra Province and how the implementation of e-government can improve the quality of public services. This research design uses a qualitative approach, because this approach allows researchers to dig up in-depth information through observations of researchers through data available on the website and online media owned by the DPMPPTSP of North Sumatra Province in serving the public regarding the quality of public services provided. The results of the study indicate that the implementation of e-government that has been applied to the DPMPPTSP of North Sumatra Province has a positive impact such as improving the quality of public services as evidenced by the data from the 2024 Annual Report and the 2024 Performance Report available on the agency's website. In general, the implementation of e-government in improving the quality of services at the Investment and One-Stop Integrated Licensing Service Office of North Sumatra Province is perceived as Very Good by the community using the service. This can be seen from the Public Satisfaction Index (IKM) obtained which ranges between 88.31 - 100. The average IKM obtained from 9 service elements is 95.43. The e-government service elements considered most satisfactory by respondents are costs/tariffs, complaint handling, suggestions and input and implementer behavior with an average value of 3.97; 3.96 and 3.88. Meanwhile, those considered less satisfactory are the completion time, system elements, mechanisms and procedures and facilities and infrastructure with an average value of 3.76; 3.79 and 3.82.